Surface plasmon-polariton resonance at diffraction of THz radiation on semiconductor gratings - Spevak, I.S.; Kuzmenko, A.A.; Tymchenko, M.; Gavrikov, V.K.; Shulga, V.M.; Feng, J.; Sun, H.B.; Kamenev, Yu.E.; Kats, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Resonance diffraction of THz hidrogen cyanide laser radiation on a semiconductor (InSb) grating is studied both experimentally and theoretically. The specular reflectivity suppression due to the resonance excitation of the THz surface plasmon-polariton is observed on a pure semiconductor grating and on semiconductor gratings covered with a thin dielectric layer. The dielectric coating of the grating results in the resonance shift and widening depending both on the layer thickness and dielectric properties. A simple analytical theory of the resonance diffraction on rather shallow gratings covered with a dielectric layer is presented, and the results are in a good accordance with the experimental data. Analytical expressions for the resonance shift and broadening are essential for the resonance properties understanding and useful for sensing data interpretation of the agents deposited on the grating surface.